P050 METHOTREXATE POLYGLUTAMATES AS BIOMARKERS OF TREATMENT RESPONSE IN PEDIATRIC INFLAMMATORY BOWEL DISEASE. (7th February 2019) - Shakhnovich, Valentina; Jausurawong, Taina; Morrow, Ryan; Becker, Mara; Funk, Ryan
Abstract: Background: Therapeutic drug monitoring methods are lacking for methotrexate (MTX), an immunomodulator used in Inflammatory Bowel Disease (IBD) treatment, alone or in conjunction with infliximab (IFX). Although studies demonstrate a lack of relationship between MTX plasma concentrations and efficacy/toxicity, recent studies in rheumatoid and juvenile idiopathic arthritis suggest a positive correlation between therapeutic response and accumulation of intracellular MTX metabolites, MTX polyglutamates (MTX-Glu). The aim of this cross-sectional investigation was to test the hypothesis that intracellular MTX-Glu are associated with therapeutic response in pediatric IBD. Methods: 21 children (5-21 years; 90% Crohn's disease), receiving combination therapy with IFX and MTX for maintenance treatment of IBD, had MTX-Glu1-6 measured in erythrocytes, using HPLC-MS/MS methodologies, and serum IFX troughs and anti-IFX antibodies (Anti-IFX) measured, using a NF-kB luciferase gene-reporter assay (ARUP Laboratories). Medical records were reviewed and disease activity determined (active vs quiescent) via consensus by 2 pediatric gastroenterologists on Physician Global Assessment. Only children on stable dosing were included (i.e., no changes to dose or interval of either drug for at least 2 IFX cycles). Nonparametric tests (e.g., Mann-Whitney U) were used to compare MTX-Glu, IFX, anti-IFX, laboratory and demographic data in children with active vs quiescent disease, and associations between MTX-Glu and parameters of interest explored via Pearson's correlation (SPSS24; α=0.05). To account for variability in standard-of-care IFX and MTX dosing, data were normalized for mg/kg and interval, as appropriate. Results: MTX dose ranged 5-25mg weekly (86% oral) and, adjusted for weight (mg/kg), correlated with total MTX-Glu accumulation (ρ=0.6; α=0.01), especially long-chain MTX-Glu3-5 (ρ=0.7; p=0.01). Children with quiescent disease (n=11) had significantly higher dose-adjusted total MTX-Glu than children with active disease (n=10), 224 ± 94.6 vs 133 ± 85.6 (p=0.04), despite receiving comparable MTX doses (0.22 ± 0.12 vs 0.31 ± 0.18 mg/kg; p=0.39). IFX troughs (μg/ml) unadjusted (24.3 ± 16.1 vs 16.7 ± 13.0) or adjusted (adj ) for IFX dose and interval (86.9 ± 59.7 vs 57.4 ± 46.8) were comparable between study groups, which were also comparable for age and disease duration (p>0.25). Neither MTX dose nor MTX-Glu correlated significantly with IFX trough or adj trough (ρ -0.09 to 0.39; p>0.1). Only 1 child, with undetectable IFX trough, had anti-IFX. Conclusions: The observed positive correlation between MTX dose and MTX-Glu suggests that MTX-Glu reflect systemic MTX exposure in IBD. Despite comparable IFX troughs, higher total MTX-Glu, particularly long-chain MTX-Glu, were associated with quiescent vs active disease, suggesting that MTX-Glu may be important markers of disease response in IBD.